Interracial friendships in college - Braz Camargo; Ralph Stinebrickner; Todd Stinebrickner (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2010)
Motivated by the reality that the benefits of diversity on a college campus will be mitigated if interracial interactions are scarce or superficial, previous work has strived to document the amount of interracial friendship interaction and to examine whether policy can influence this amount. In this paper we take advantage of unique longitudinal data from the Berea Panel Study to build on this previous literature by providing direct evidence about the amount of interracial friendships at different stages of college and by providing new evidence about some of the possible underlying reasons for the observed patterns of interaction. We find that, while much sorting exists at all stages of college, black and white students are, in reality, very compatible as friends; randomly assigned roommates of different races are as likely to become friends as randomly assigned roommates of the same race. Further, we find that, in the long-run, white students who are randomly assigned black roommates have a significantly larger proportion of black friends than white students who are randomly assigned white roommates, even when the randomly assigned roommates are not included in the calculation of the proportions. This last result contradicts previous findings in the literature.
Keywords: 330; Studierende; Hochschule; Ethnische Beziehungen; USA